Trinidad and Tobago, B.W.I - Simpson, Keith (My University, 2009)
Description on the back of postcard: “Bull carts are still driven by peasants on Trinidad sugar estates.”
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Draft animals; Oxen; Sugar workers